2020
DOI: 10.3390/nano10122536
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrahigh Sensitive Paper-Based Pressure Sensor with Intelligent Thermotherapy for Skin-Integrated Electronics

Abstract: Porous microstructure pressure sensors that are highly sensitive, reliable, low-cost, and environment-friendly have aroused wide attention in intelligent biomedical diagnostics, human–machine interactions, and soft robots. Here, an all-tissue-based piezoresistive pressure sensor with ultrahigh sensitivity and reliability based on the bottom interdigitated tissue electrode and the top bridge of a microporous tissue/carbon nanotube composite was proposed. Such pressure sensors exhibited ultrahigh sensitivity (≈1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…The squared correlation coefficient (R 2 ) of the Langmuir model was closer to 1, which was much higher than the R 2 of the Freundlich model. This phenomenon indicates that the process of Cr(VI) removal by Cu/Fe bimetallic nanoparticles is a monolayer adsorption, with Cr(VI) homogeneously distributed on the adsorption sites on the material surface 50 , 53 . The separation factor R L is an important parameter of the Langmuir model, defining by the following equation: where K L is the Langmuir constant (L mg −1 ), and C 0 is the initial concentration of Cr(VI) solution.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The squared correlation coefficient (R 2 ) of the Langmuir model was closer to 1, which was much higher than the R 2 of the Freundlich model. This phenomenon indicates that the process of Cr(VI) removal by Cu/Fe bimetallic nanoparticles is a monolayer adsorption, with Cr(VI) homogeneously distributed on the adsorption sites on the material surface 50 , 53 . The separation factor R L is an important parameter of the Langmuir model, defining by the following equation: where K L is the Langmuir constant (L mg −1 ), and C 0 is the initial concentration of Cr(VI) solution.…”
Section: Resultsmentioning
confidence: 96%
“…In our experiment, the values of R L with different initial Cr(VI) concentrations were close to zero and decreased with increasing initial concentrations. This indicated that the adsorption process was favorable, and there was a strong affinity between Cr(VI) ions and Cu/Fe bimetallic nanoparticles 43 , 53 .…”
Section: Resultsmentioning
confidence: 98%
“…However, the synthesized PANI can be further explored by stacking the multiple layers of the sensor, which could spontaneously form microstructure air gaps between the layers, forming a conductive network between the layers. Since we have explored PANI/SLS for humidity sensing performance using a single layer of the sensor, we restricted the investigation to a single sensor layer for pressure sensing [75][76][77]. The poor sensitivity of the sensor against different pressure conditions suggests excellent selectivity of the sensor for humidity sensing.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…Since we have explored PANI/SLS for humidity sensing performance using a single layer of the sensor, we restricted the investigation to a single sensor layer for pressure sensing. [75][76][77] The poor sensitivity of the sensor against different pressure conditions suggests excellent selectivity of the sensor for humidity sensing. High sensitivity, selectivity, repeatability, lightweight, ease of fabrication, improved electrical properties and quick response along with low hysteresis could make the PANI/SLS coated paper sensor a potential material for humidity sensing application.…”
Section: Materials Advances Papermentioning
confidence: 99%
“…Taehoon Lee, Yunsung Kang, Kwanhun Kim, Sangjun Sim, Kyubin Bae, Yeunjun Kwak, Wonkeun Park, Minhyeong Kim, and Jongbaeg Kim* DOI: 10.1002/admt.202100428 and supercapacitors [10] that apply the aforementioned properties of paper have been proposed and experimentally verified. Among various applications, paperbased tactile sensors that detect applied pressure have also garnered significant attention, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] regardless of their sensing principles based on changes in piezoresistivity, capacitance, and contact resistance. This is because paper can be utilized as a pressure-sensing structure owing to its high porosity and deformability.…”
Section: All Paper-based Multilayered Inkjet-printed Tactile Sensor I...mentioning
confidence: 99%